Hansan = Hansan : rising dragon [videorecording (DVD)] - Kim, Han-min, 1969-; Yoon, Hong-ki; Lee, Na-ra; Park, Hae-il, 1977-; Pyŏn, Yo-han, 1986-; An, Sŏng-gi, 1952- (Well Go USA Entertainment, 2022)
The legend of the invincible fleet begins! Set five years before the epic battle depicted in The Admiral: Roaring Currents, Hansan: Rising Dragon is based on the true historical naval engagement, Battle of Hansan Island. In July 1592, admiral Yi Sun-sin and his Korean naval fleet face off against invading Japanese naval warships. Falling into crisis, the admiral must use his secret weapon to change the tides in this epic battle at sea.